Barclays the business of banking, 1690-1996 - Ackrill, Margaret (Cambridge University Press, 2001)
This is a history of one of the world's most famous financial institutions from its foundation as a private Quaker partnership in 1690 to 1996. Over the course of its history, Barclays has been the largest bank in the world, in Africa, and in Britain. It makes a major contribution to the economic and social history of modern Britain and the contemporary business world.